2022
DOI: 10.1101/2022.05.19.492695
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved and variable responses of the HEAT SHOCK FACTOR transcription factor family in maize and Setaria viridis

Abstract: Responding to the environment is a core aspect of plant growth and development. Mounting an effective response is important for plants to balance growth and survival. The HEAT SHOCK FACTOR (HSF) transcription factor family is a central and required component of plant heat stress responses and acquired thermotolerance. The HSF family has dramatically expanded in plant lineages, often including a repertoire of 20 or more genes. Here we assess the composition and heat responsiveness of the HSF family in Setaria v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…This study also included profiles of samples with a 24-hour recovery period following the stress, revealing that chromatin accessibility often reverts to prestress configurations (110). An analysis of heat shock factors in maize and Setaria indicated that while many genes are strongly induced by heat stress, chromatin accessibility variation in response to heat stress is limited (94). However, a combined analysis of three-dimensional spatial organization and chromatin accessibility uncovered dynamic changes in the response to heat stress in rice (72).…”
Section: Environmental Responsesmentioning
confidence: 99%
“…This study also included profiles of samples with a 24-hour recovery period following the stress, revealing that chromatin accessibility often reverts to prestress configurations (110). An analysis of heat shock factors in maize and Setaria indicated that while many genes are strongly induced by heat stress, chromatin accessibility variation in response to heat stress is limited (94). However, a combined analysis of three-dimensional spatial organization and chromatin accessibility uncovered dynamic changes in the response to heat stress in rice (72).…”
Section: Environmental Responsesmentioning
confidence: 99%
“…Prior studies have found evidence for enrichment of the HSF binding site motif at up-regulated genes in Arabidopsis 13 , maize 14 and rice 15 . Some HSFs are stably expressed and become activated in response to heat stress, while many other members of this family are themselves transcriptionally activated in response to heat stress 12,16,17 . Several other transcription factors and cis -regulatory elements have also been implicated in the response to heat stress 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found evidence for enrichment of the HSF binding site motif at upregulated genes in Arabidopsis [13], maize [14], and rice [15]. Some HSFs are stably expressed and become activated in response to heat stress, while many other members of this family are themselves transcriptionally activated in response to heat stress [12,16,17]. Several other transcription factors and cis-regulatory elements have also been implicated in the response to heat stress [18].…”
mentioning
confidence: 99%